2001
DOI: 10.1038/sj.sc.3101174
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for thoracic spinal stenosis

Abstract: Objectives: To describe the underlying causes, surgical results and prognostic factors in thoracic stenosis causing myelopathy. Methods: The underlying causes and surgical results were analyzed retrospectively in 28 cases of thoracic spinal stenosis which caused myelopathy. Degenerative spondylosis was the most common cause, and three cases were associated with systemic diseases. Decompressive laminectomy was performed in 24 cases, anterior decompression in ®ve cases, and combined decompression in one case. Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 22 publications
2
59
2
Order By: Relevance
“…Early diagnosis and treatment are important for the postoperative functional prognosis. It is reported that the persistence of residual spasticity at follow-up may be due to irreversible changes within the cord that is caused by the significant cord compression and the delay between the onset of initial symptoms and surgical decompression [2,9,12,14]. In our series, the symptom duration was not related to the surgical outcome statistically, but, especially the short symptom duration, less than 6 months, was a relatively favorable factor to the surgical outcome.…”
Section: Discussioncontrasting
confidence: 44%
“…Early diagnosis and treatment are important for the postoperative functional prognosis. It is reported that the persistence of residual spasticity at follow-up may be due to irreversible changes within the cord that is caused by the significant cord compression and the delay between the onset of initial symptoms and surgical decompression [2,9,12,14]. In our series, the symptom duration was not related to the surgical outcome statistically, but, especially the short symptom duration, less than 6 months, was a relatively favorable factor to the surgical outcome.…”
Section: Discussioncontrasting
confidence: 44%
“…In addition to the anatomical difference relating to mechanical stress involving constraints on the articular processes during segmental motion, this difference may also be attributed to increased instability in lower thoracic spine. 41,55,57 Compared with the middle thoracic spine, it seems to be more particularly easy to make degenerative processes on the lower thoracic spine owing to the high tensile force present on the posterior column. 22,55 Maigne et al 55 reported that OLF occurred most frequently at the lower thoracic spine especially at the thoracolumbar junction, and its appearance correlated with a unique orientation of the facet joints that generated increased rotatory instability and micromotion.…”
Section: Discussionmentioning
confidence: 99%
“…26,28,57 Surgery is the only treatment that can adequately address the significant compression of neurologic structures caused by OLF. 1,29,62-64 The goal of surgical intervention is to excise the ossified segments and provide sufficient decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies 13,14 have reported that in patients with a spinal degenerative disease, the shorter the duration of the disease is, the more likely the postoperative results are to be excellent. However, the duration of disease is estimated based on information obtained from the patients, and therefore it is often uncertain.…”
Section: Discussionmentioning
confidence: 99%